The use of nano-structured cellulose to improve plywood: A review - L.C. Lirya Silva; F.O. Lima; S.N. Monteiro; A.R.G. Azevedo; A.L. Christoforo; B.S. Ferreira; D. Goveia; C.I. de Campos (Journal of Materials Research and Technology)
The great availability of forest resources in Brazil enables the constant growth of industrial sectors that employ wood as a raw material. Hence, several products and production techniques were developed to maximize the availability of this resource, giving rise to wood-based panels and highlighting plywood as a structural use. The use of nanomaterials appears as an alternative to improve wood products. Among these nanomaterials, nano-structured cellulose has stood out for its high strength and stiffness. In this sense, this article aims to present a literature review regarding the use and effects of nanocellulose in plywood panels based on a systematic searching of keywords related to nano-structured cellulose in plywood employment on the Scopus website. An initial search from 1950 was performed with the keyword “cellulose.” A subsequent search included the acronym “plywood” combined with terms such as “nanocellulose,” “cellulose nanocrystals,” and “cellulose nanofibrils.” The Virtual Operating System (VOS) Viewer was used to develop a graphical mapping. The main authors were selected for an in-depth analysis of their results. Thus, it was concluded that most authors observed, for both nanocrystals and cellulose nanofibers, an increase in the adhesive viscosity as well as an improvement in the mechanical properties, especially regarding tensile shear strength and bonding quality, for 0.038, 1, 3, and 5% of nanocellulose. Some authors have also achieved a reduction in formaldehyde emissions. Therefore, using nanofibers and cellulose nanocrystals can be considered sustainable alternatives for the wood-based panel industry, improving the mechanical properties and reducing toxic emissions.